Factors negatively affecting quality of life in geriatric patients: review - Marcinkowski, Krzysztof; Muras, Mateusz; Michalik, Maciej; Lorenc, Tomasz; Mikszta, Natalia; Mikszta, Jakub; Marcinkowska, Julia; Kantor, Karolina (GMS Hygiene and Infection Control)
Introduction: The aging process is accompanied by a variety of challenges that significantly impact the quality of life and overall well-being of older adults. This study explores several key factors that negatively affect seniors, including loneliness, frailty syndrome, falls, polypharmacy, urinary incontinence, chronic pain, and malnutrition. Method: The PubMed and Google Scholar databases were searched to find scientific articles in which the terms “elderly”, and “quality of life” appear in the title, abstract, or keywords. Results: Loneliness emerges as a critical issue, contributing to mental health problems such as depression and cognitive decline. Falls, a leading cause of injury among older adults, often result in long-term physical and psychological consequences. Polypharmacy, while intended to manage multiple chronic conditions, increases the risk of adverse drug reactions and medication non-adherence. Frailty syndrome reduces a patient’s susceptibility to stressors. Urinary incontinence, often stigmatized, affects physical comfort and social interactions, reducing the dignity of those affected. Chronic pain disrupts daily functioning and exacerbates feelings of helplessness, while malnutrition undermines physical health, leading to frailty and increased susceptibility to illnesses. All of these factors have their impact on quality of life in older adults. Conclusions: The study identifies key factors negatively affecting the quality of life in older adults, including physical, psychological, and social challenges that require comprehensive and targeted interventions.